2016
DOI: 10.1055/s-0036-1594015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Obesity with Child Cerebral Palsy or Death

Abstract: The primary aim of this study was to determine if there is an association between maternal obesity and cerebral palsy or death in children. This is a retrospective cohort analysis of a randomized controlled clinical trial previously performed by the Maternal-Fetal Medicine Units Network. Women in the original trial were included if at high risk for preterm delivery. The present study included singletons enrolled in the original study with complete data. Obese and nonobese women were compared. A secondary analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Obesity is becoming an epidemic health problem. This trend is particularly true for maternal obesity and overweight, which may be associated with adverse obstetric complications[ 1 , 2 ]. Maternal obesity is associated with low Apgar scores at 5 minutes[ 2 , 3 ], preterm birth[ 4 ], low birth weight, periventricular leukomalacia (PVL)[ 5 ], autism spectrum disorders (ASDs)[ 6 , 7 ], and intellectual disability[ 8 ], which could alter the offspring’s neurodevelopmental outcomes[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obesity is becoming an epidemic health problem. This trend is particularly true for maternal obesity and overweight, which may be associated with adverse obstetric complications[ 1 , 2 ]. Maternal obesity is associated with low Apgar scores at 5 minutes[ 2 , 3 ], preterm birth[ 4 ], low birth weight, periventricular leukomalacia (PVL)[ 5 ], autism spectrum disorders (ASDs)[ 6 , 7 ], and intellectual disability[ 8 ], which could alter the offspring’s neurodevelopmental outcomes[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity and overweight are the leading cause of public health problems. More than half of women receiving prenatal care in the United States are overweight or obese[ 12 ], and maternal obesity and overweight are epidemic in Sweden[ 13 ] and other countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women with gestational diabetes have an increased risk of pregnancy complications; however, the risks are more in obese women with obese [9]. Another study by McPherson et al showed an increased risk of adverse delivery outcomes in the subgroup of morbidly obese women [10].…”
Section: Introductionmentioning
confidence: 99%